Smart farming technologies for sustainable agriculture: A review of the promotion and adoption strategies by smallholders in Sub-Saharan Africa - Bashiru, Motin; Ouedraogo, Mathieu; Ouedraogo, Adama; Läderach, Peter (MDPI, 2024)
Small-scale farmers in sub-Saharan Africa (SSA) need to adopt and consistently practice sustainable agriculture to ensure sustainable livelihoods and food security. However, the adverse effects of climate change are threatening the achievement of this goal. Therefore, farmers within the sub-region need to embrace climate-smart agriculture (CSA) as a means for climate change adaptation and mitigation. This study was conducted to understand, on the one hand, how smart farming technologies are being promoted in sub-Saharan Africa, and on the other hand, how farmers are adopting the prevailing technologies. The Preferred Reporting Items for Systematic Reviews (PRISMA) procedures were followed to identify 48 scientific papers in sub-Saharan Africa. It was found that promoters of smart farming technologies in sub-Saharan Africa include CGSpace, FAO, National Research Institutions, individual researchers, local institutions, and private institutions. The approach to the smart farming technology discourse in sub-Saharan Africa starts by building on efforts to sustain CSA practices with a gradual shift towards the fourth agriculture revolution innovations. Even where there are efforts to push beyond conventional CSA practices by the private sector, farmers’ responses are still low. It is recommended that any intervention to promote modern smart farming technologies to smallholders should build on conventional CSA practices.